Karakteristik Fisik dan Displacement Value Supositoria Neomisin Sulfat berbasis PEG - Milala, Alasen Sembiring; Pradana, Aditya Trias; Boehe, Andrew Pierce (Indonesian Research Gateway)
Physical characteristic and the Displacement Value of neomycin sulfate in suppository with various composition of PEG 400-4000 as it carrier has been studied. Displacement Value has been determined to adjust the weight of suppositories that varies due to the density difference among drug substance and its carriers. The method used in the determination of Displacement Value is the Moody method. Beside the displacement value, we have also evaluated the physical characteristic of suppository that has been produced, such as weight uniformity, hardness, macro and micro melting point and liquefaction ability. The results shows that all measurements meet the requirements and the Displacement Value of Neomycin sulfate obtained from Moody method, was 0.96.Keywords : Suppository, Displacement Value, Neomycin sulfate.